Low-cost microcontact printing for direct enzyme patterning on paper - Ahmad, Siti Khadijah; Arris, Farrah Aida; Wan Salim, Wan Wardatul Amani (2015)

(untitled)
In this study, an easy, low-cost, and straightforward method to pattern and directly control the amount of enzyme deposited on paper using microcontact printing was successfully developed without the need for a cleanroom facility. Full characterization was done to evaluate the effectiveness of this approach, from the fabrication of a master stamp with controlled width spacing of 20, 50, and 100 μm using a vertical micromilling method to the stamping of glucose oxidase (GOx) onto papers with different porosity. To prove the concept of direct enzyme patterning, GOx is patterned on paper impregnated with anthocyanin, a water-soluble vacuolar pigment. Anthocyanin contains glucose covalently attached to the flavonoid backbone and is able to give a colorimetric change from purple to red to indicate successful deposition of GOx owing to the product of gluconic acid. Stamping process parameters were varied in terms of force (8, 20, 40, and 50 g) and time (5, 30, and 60 s) to transfer GOx from soft stamp to porous paper. Results show that the paper with the highest porosity stamped using a 200 g load for 5 s, gives the best result in terms of patterns and successful transfer of enzyme onto the paper. This study suggests that the fabrication of a master stamp using inexpensive micromilling methods can produce a soft stamper that can pattern a bioactive enzyme.